Among-individual and within-individual variation in seasonal migration covaries with subsequent reproductive success in a partially migratory bird. Issue 1931 (22nd July 2020) - Reid, Jane M.; Souter, Moray; Fenn, Sarah R.; Acker, Paul; Payo-Payo, Ana; Burthe, Sarah J.; Wanless, Sarah; Daunt, Francis
Abstract : Within-individual and among-individual variation in expression of key environmentally sensitive traits, and associated variation in fitness components occurring within and between years, determine the extents of phenotypic plasticity and selection and shape population responses to changing environments. Reversible seasonal migration is one key trait that directly mediates spatial escape from seasonally deteriorating environments, causing spatio-seasonal population dynamics. Yet, within-individual and among-individual variation in seasonal migration versus residence, and dynamic associations with subsequent reproductive success, have not been fully quantified. We used novel capture-mark-recapture mixture models to assign individual European shags ( Phalacrocorax aristotelis ) to 'resident', 'early migrant', or 'late migrant' strategies in two consecutive years, using year-round local resightings. We demonstrate substantial among-individual variation in strategy within years, and directional within-individual change between years. Furthermore, subsequent reproductive success varied substantially among strategies, and relationships differed between years; residents and late migrants had highest success in the 2 years, respectively, matching the years in which these strategies were most frequently expressed. These results imply that migratory strategies can experience fluctuating reproductive selection, and that flexible expression of migration can be partially aligned with reproductive outcomes. Plastic seasonal migration could then potentially contribute to adaptive population responses to currently changing forms of environmental seasonality.